Lectores, editores y cultura impresa en Colombia, siglos XVI-XXI - Guzmán Méndez, Diana Paola; Marín Colorado, Paula Andrea; Murillo Sandoval, Juan David; Pineda Cupa, Miguel Ángel (CERLALC, Centro Regional para el Fomento del Libro en América Latina y el Caribe : Editorial Utadeo, 2018)
This volume examine the conditions and problems of the production, circulation and uses of books in Colombia. The texts reconstruct various moments in the development of a local printed culture since the 16th century, before the arrival of the printing press, the dynamism of the printed world during the 19th century, as well as what happened in the 20th century, when the moment of greater editorial modernization and expansion of the Colombian reading groups took place, covering until the dawn of the 21st century and the new technological and legal challanges faced by the editorial industry.